Move two: establishing a niche - Wasima Shehzad (Ibérica, 2008)
The significant purpose of the author in the Introduction of a research article is to convince the reader about the importance of the work to be presented. To achieve this end, a convincing “niche” needs to be built by evaluating, rejecting or indicating gaps in previous related work. The purpose of “establishing a niche” is to emphasize the current research project presented by the author. The present paper investigates how Computer scientists use this obligatory step of “Create a Research Space” (CARS) model (Swales & Feak, 1994 & 2004) to highlight their own research work. This paper not only compares the results with other similar studies but also presents an in-depth analysis of various types of gap statements used in Computer Science research article Introductions. The issue of cyclicity of this step and the linguistic indicators used for the establishment of “niche” (the gap statements) are both discussed.